Specifics of CSR Practices During the Crisis Caused by Covid-19 - Polish Experience - Marta MISZCZAK (Communications of International Proceedings, 2021)
The economic and social situation caused by the COVID-19 pandemic, may contribute to companies focusing less on socially responsible practices. The experience of the previous global financial crisis in 2008 shows that despite difficulties, companies did not abandon socially responsible practices, but some of them reduced the number of CSR projects. It is worth observing how the situation will develop this time. The aim of the article is to characterize and analyse selected CSR practices undertaken by companies during the crisis caused by the SARS-CoV-2 virus pandemic, and answer to a question about the specificity of these activities. The material was discussed in relation to Polish realities. The analysis of the problem is based on literature of the subject and reference materials such as study reports and a compilation of socially responsible practices of sixty-five (65) companies, prepared by the Polish Ministry of Funds and Regional Policy.  The conclusions from the analysis allow to conclude that despite the crisis, companies have not abandoned CSR practices, but under the influence of the crisis, the direction and character of their activities in the area of CSR have changed.
Keywords: CSR; corporate social responsibility in crisis; COVID-19